Oral nimodipine reduces prostaglandin and thromboxane production by arteries chronically exposed to a periarterial haematoma and the antifibrinolytic agent tranexamic acid. Issue 6 (June 1987) - Pickard, J D; Walker, V; Vile, J; Perry, S; Smythe, P J; Hunt, R
Abstract : The calcium antagonist nimodipine blocks the effects of many vasoconstrictors of cerebrovascular smooth muscle and may reduce the incidence of delayed cerebral ischaemia following subarachnoid haemorrhage though not necessarily by inhibiting the development of angiographic cerebral vasospasm. Post-haemorrhagic CSF contains abnormally large quantities of various eicosanoids that partly reflect enhanced production by cerebral arteries. Does nimodipine affect this process? The extra-arterial and intra-arterial production of PG6 keto-F1 alpha, PGE2, PGF2 alpha and TXB2 were measured in perfused common carotid arteries taken from rabbits in which the arteries had been ensheathed by blood clot in vivo for 7 days. All rabbits were given the antifibrinolytic agent tranexamic acid to retard resolution of the clot, and half were given oral nimodipine (2 mg/kg/day) for 10 days. Nimodipine significantly reduced the extra-arterial production of TXB2 during the third and fourth hours of perfusion and, less consistently, the production of PGF2 alpha, PGE2 and PG6 keto-F1 alpha. Lutrol, the solvent for nimodipine, had no such effect.